Influence of Chromatic Ambient Light over Colour Luminance Contrast on Projection Screen - Masiokas, S.; Kriuglaitė, M. (Elektronika ir Elektrotechnika, 2009)
Digital image projection on screen is the main way of information visualization entrenched in science, teaching and business areas. And though technique and equipment for visualization has probably reached the peak today, visibility on screen is influenced by ambient light. It is impossible avoid ambient light, but its influence can be reduced by using least ambient light sensitive colour combinations. Analysis of influence of chromatic ambient light over colour luminance contrast for different task and beckground colours, showed that there are Black and Blue usable tasks in White background and White, Green, Cyan and Yellow tasks for Black background. Tasks of any colour is most sensitive to White and Yellow ambient light and least sensitive to Blue, Red and Magenta ambient light. Ill. 6, bibl. 7 (in English; summaries in English, Russian and Lithuanian).